2012
DOI: 10.5370/jeet.2012.7.3.342
|View full text |Cite
|
Sign up to set email alerts
|

A New Moving-magnet Type Linear Actuator utilizing Flux Concentration Permanent Magnet Arrangement

Abstract: -This paper presents a moving-magnet type linear actuator designed by using flux concentration type permanent magnet arrangement, which can generate higher magnetic flux density in air-gap. In this construction, detent force which is induced by both slot-effect and end-effect becomes larger due to strong attractive forces. To reduce cogging force we have employed a modular mover structure of two magnetic pole sections connected with a center yoke. The improved motor performance is demonstrated with the prototy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In recent years, linear motors have been widely used in transportation systems and industrial application with significant advantages that not need to launch a mechanical converter from rotational torque to linear force [1][2][3][4][5][6]. The conventional permanent-magnet (PM) linear motor exhibits higher efficiency and high power factor than the linear induction motor.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, linear motors have been widely used in transportation systems and industrial application with significant advantages that not need to launch a mechanical converter from rotational torque to linear force [1][2][3][4][5][6]. The conventional permanent-magnet (PM) linear motor exhibits higher efficiency and high power factor than the linear induction motor.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the PMA has received much attention lately for the application of a circuit breaker [1][2][3][4]9]. Many researchers have been conducted the research on the PMA as reported in [1,2,[5][6][7][10][11][12][13][14][15][16][17] for several decades. The PMA requires a rare earth permanent magnet for high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Orbital friction vibration actuators (OFVA) have become a core part of orbital friction welding technology whose applications fall into many industries [1][2][3][4]. As the force-supply unit of the orbital friction welding machine, the OFVA should generate higher thrust force when it operates in relatively high frequency.…”
Section: Introductionmentioning
confidence: 99%